2022
DOI: 10.1111/jne.13122
|View full text |Cite
|
Sign up to set email alerts
|

The estrous cycle and 17β‐estradiol modulate the electrophysiological properties of rat nucleus accumbens core medium spiny neurons

Abstract: The nucleus accumbens core is a key nexus within the mammalian brain for integrating the premotor and limbic systems and regulating important cognitive functions such as motivated behaviors. Nucleus accumbens core functions show sex differences and are sensitive to the presence of hormones such as 17β-estradiol (estradiol) in normal and pathological contexts. The primary neuron type of the nucleus accumbens core, the medium spiny neuron (MSN), exhibits sex differences in both intrinsic excitability and glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 148 publications
(406 reference statements)
0
5
0
Order By: Relevance
“…A similar increase in miniature EPSC frequency but not amplitude and no change in the paired-pulse ratio of evoked EPSCs were also observed in NAcc medium spiny neurons following experimenter-delivered or non-contingent cocaine injections and several weeks of withdrawal in both male and female rats, with a more robust effect observed in females [33]. Studies in drug-naïve animals have also shown that estrous cycle fluctuations alone can influence neuronal physiology in different brain regions [34]. Indeed, we also observed an increase in sEPSC amplitude in estrus females that was independent of drug exposure (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…A similar increase in miniature EPSC frequency but not amplitude and no change in the paired-pulse ratio of evoked EPSCs were also observed in NAcc medium spiny neurons following experimenter-delivered or non-contingent cocaine injections and several weeks of withdrawal in both male and female rats, with a more robust effect observed in females [33]. Studies in drug-naïve animals have also shown that estrous cycle fluctuations alone can influence neuronal physiology in different brain regions [34]. Indeed, we also observed an increase in sEPSC amplitude in estrus females that was independent of drug exposure (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Further, if DA is conserved during food restriction, and restoration of DA utilization by environmental enrichment is key to effects observed in males, the marked fluctuations in DA utilization and receptor density across stages of the estrous cycle [ 85 87 ] may create a ‘noisy’ background that obscures the effect of environmental enrichment. Additional mechanistic complication may arise from the variation in glutamate utilization, AMPA receptor expression [ 88 ], MSN intrinsic excitability, and amplitude and frequency of sEPSCs across phases of the estrous cycle [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Males and females express ERs and aromatase in adulthood; however, it is not known whether ERs and aromatase expression differ by sex or estrous cycle phase [102, 135]. Our original study found no difference in the sensitivity to rapid estradiol action upon mEPSC frequency between different estrous cycle phases; thus, we did not assess the estrous cycle as an experimental variable in this brief report.…”
Section: Discussionmentioning
confidence: 99%